History, literature, and society in the book of Acts - Witherington, Ben, III, 1951- (Cambridge ; New York : Cambridge University Press, 1996)
These seminal essays introduce the reader to the interdisciplinary approach of recent New Testament scholarship which is affecting the way the Book of Acts is studied and interpreted. Insights from the social sciences, narratological studies, Greek and Roman rhetoric and history, and classics, set the Acts of the Apostles in its original historical, literary and social context; these methods of interpretation have only recently been applied to biblical study in a systematic way. The discussions from a shared general perspective range over genre and method, historical and theological problems, and issues of literary criticism. History, Literature and Society in the Book of Acts is an interesting and valuable overview of some of the chief preoccupations of current biblical studies with contributions from leading scholars in the Old and New Testaments and the history of antiquity. -- Publisher's description
Part I. Issues of Genre and Method: -- 1. In the shadow of Thucydides / W.J. McCoy -- 2. How history should be written / C.K. Barrett -- 3. The Acts of the Apostles: monograph or bios? / Charles H. Talbert -- 4. The preface to Acts and the historians / Loveday C .A. Alexander -- 5. The future of the past / Jacob Jervell -- Part II. Historical and Theological Difficulties in Acts: -- 6. Acts 6.1-8.4: division or diversity? / Craig C. Hill -- 7. James and the Gentiles (Acts 15.13-21) / Richard Bauckham -- 8. Kerygmatic summaries in the speeches of Acts / Richard Bauckham -- 9. The 'script' of the scriptures in Acts: suffering as God's 'plan' with the world for the 'release of sins' / David P. Moessner -- 10. Luke's social location of Paul: cultural anthropology and the status of Paul in Acts / Jerome H. Neyrey -- Part III. Issues of Literary Criticism: -- 11. Internal repetition in Luke-Acts: contemporary narratology and Lukan historiography / Joel B. Green -- 12. Luke's characterising use of the Old Testament in the Book of Acts / Bill T. Arnold -- 13. Editing the good news: some synoptic lessons for the study of Acts / Ben Witherington, III -- 14. The means of absent ends / Wm. F. Brosend, II
Includes bibliographical references and index
Keywords: Bible. -- Criticism, interpretation, etc